Comparison of Error Protection Methods for Audio-Video Broadcast over DVB-H. (24th June 2007) - Hannuksela Hannuksela, Miska M. Miska M.; Malamal Vadakital Malamal Vadakital, Vinod Kumar Vinod Kumar; Jumisko-Pyykkö Jumisko-Pyykkö, Satu Satu
Abstract : The paper discusses methods for robust audio-video broadcast over the digital video broadcasting-handheld (DVB-H) system. DVB-H includes a link-layer forward error correction (FEC) scheme known as multiprotocol encapsulation (MPE) FEC, which provides equal error protection (EEP) to the transmitted media streams. Several approaches for unequal error protection (UEP) have been proposed in the literature, and the applicability of some of them to DVB-H is analyzed in the paper. A link-layer UEP method based on priority segmentation of the media streams is chosen for more detailed analysis. According to the method, audio and the most important coded video pictures are protected by MPE-FEC more robustly compared to the remaining coded pictures. In order to compare EEP and UEP in a DVB-H environment, an error-prone DVB-H channel was simulated, audio-visual clips were sent through it, and a comprehensive subjective quality evaluation was conducted in a controlled laboratory environment. The results of the subjective evaluation revealed that the use of UEP improves the subjective quality of some test clips noticeably when the channel conditions were severe, while in other tested channel conditions and clips, UEP and EEP performed equally well.